Exogenous 5-aminolevulenic acid promotes seed germination in Elymus nutans against oxidative damage induced by cold stress. - Juanjuan Fu; Yongfang Sun; Xitong Chu; Yuefei Xu; Tianming Hu (PLoS ONE, 2014)
The protective effects of 5-aminolevulenic acid (ALA) on germination of Elymus nutans Griseb. seeds under cold stress were investigated. Seeds of E. nutans (Damxung, DX and Zhengdao, ZD) were pre-soaked with various concentrations (0, 0.1, 0.5, 1, 5, 10 and 25 mg l(-1)) of ALA for 24 h before germination under cold stress (5°C). Seeds of ZD were more susceptible to cold stress than DX seeds. Both seeds treated with ALA at low concentrations (0.1-1 mg l(-1)) had higher final germination percentage (FGP) and dry weight at 5°C than non-ALA-treated seeds, whereas exposure to higher ALA concentrations (5-25 mg l(-1)) brought about a dose dependent decrease. The highest FGP and dry weight of germinating seeds were obtained from seeds pre-soaked with 1 mg l(-1) ALA. After 5 d of cold stress, pretreatment with ALA provided significant protection against cold stress in the germinating seeds, significantly enhancing seed respiration rate and ATP synthesis. ALA pre-treatment also increased reduced glutathione (GSH), ascorbic acid (AsA), total glutathione, and total ascorbate concentrations, and the activities of superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX) and glutathione reductase (GR), whereas decreased the contents of malondialdehyde (MDA) and hydrogen peroxide (H2O2), and superoxide radical (O2•-) release in both germinating seeds under cold stress. In addition, application of ALA increased H+-ATPase activity and endogenous ALA concentration compared with cold stress alone. Results indicate that ALA considered as an endogenous plant growth regulator could effectively protect E. nutans seeds from cold-induced oxidative damage during germination without any adverse effect.